Through the Looking-Glass: Psychoneuroimmunology and the Microbiome-Gut-Brain Axis in the Modern Antiretroviral Therapy Era. Issue 8 (28th October 2022) - Carrico, Adam W.; Cherenack, Emily M.; Rubin, Leah H.; McIntosh, Roger; Ghanooni, Delaram; Chavez, Jennifer V.; Klatt, Nichole R.; Paul, Robert H.
ABSTRACT: Objective: Depression, substance use disorders, and other neuropsychiatric comorbidities are common in people with HIV (PWH), but the underlying mechanisms are not sufficiently understood. HIV-induced damage to the gastrointestinal tract potentiates residual immune dysregulation in PWH receiving effective antiretroviral therapy. However, few studies among PWH have examined the relevance of microbiome-gut-brain axis: bidirectional crosstalk between the gastrointestinal tract, immune system, and central nervous system. Methods: A narrative review was conducted to integrate findings from 159 articles relevant to psychoneuroimmunology (PNI) and microbiome-gut-brain axis research in PWH. Results: Early PNI studies demonstrated that neuroendocrine signaling via the hypothalamic-pituitary-adrenal axis and autonomic nervous system could partially account for the associations of psychological factors with clinical HIV progression. This review highlights the need for PNI studies examining the mechanistic relevance of the gut microbiota for residual immune dysregulation, tryptophan catabolism, and oxytocin release as key biological determinants of neuropsychiatric comorbidities in PWH (i.e., body-to-mind pathways). It also underscores the continued relevance of neuroendocrine signaling via the hypothalamic-pituitary-adrenal axis, autonomic nervous system, and oxytocin release in modifying microbiome-gut-brain axis functioning (i.e., mind-to-body pathways). Conclusions: Advancing our understanding of PNI and microbiome-gut-brain axis pathways relevant to depression, substance use disorders, and other neuropsychiatric comorbidities in PWH can guide the development of novel biobehavioral interventions to optimize health outcomes. Recommendations are provided for biobehavioral and neurobehavioral research investigating bidirectional PNI and microbiome-gut-brain axis pathways among PWH in the modern antiretroviral therapy era.